Damage assessment of different FDM-processed materials adopting Infrared Thermography (Fracture and Structural Integrity, 2022)
The use of components obtained through the additive manufacturing (AM) technique has become increasingly widespread in recent years, playing a central role in industrial production, and in particular in some fields such as automotive, biomedical, aerospace and electronics. Among all AM techniques, FDM (Fused Deposition Modelling) represents the most used printing technique to produce polymeric and composite components, thanks to the flexible printing process, the low cost and the diversity of the materials adopted. The aim of the present work concerns the comparison between the mechanical properties of three plastic materials printed with the FDM technique (polylactic acid PLA, polyethylene terephthalate glycol-modified PETG and Acrylonitrile-butadiene-styrene ABS) using an Original Prusa i3 MK3S, by varying the raster angle between 0°, 45° and 90° degrees. Infrared Thermography has been adopted to monitor the temperature evolution during static tensile tests and to assess stress level that can initiate damage within the material. Failure analysis was performed to correlate the mechanical behaviour with the microstructural characteristics of the materials.
Keywords: 3D printing; DfAM; Microstructure; PLA; ABS; PETG